Criação de varas do trabalho específicas para julgamento de processos tramitados pelo procedimento sumaríssimo como mecanismo de efetivação da prestação jurisdicional do Poder Judiciário trabalhista - Thomé, Sorean Mendes da Silva (2010)
The aim of this research is to analyze the Law number 9.957/2000, which established the process accelerated, in the process of labor. It seeks to identify models of procedures used in the labor lawsuit, mainly at procedure accelerated and its efficiency within the organizational structure of the labour court. It also shows the necessity of compliance with law number 9.957/2000 as a feasible tool for effective adjudication of the labour Court in cases with amount estimated is below forty salaries. In order to achieve these aim, we approached initially background´s law aspects to reach at justice, constitutional principles of reasonable timing of proceeding and legal certainty, so the comprehension and union of labour laws. Another aspect of this research shows the search for revolutionary changes in the organization structure of the labour court for a hole applicability of the procedure accelerated, due to overload of cases in progress at court. We attempt to analyze the labour court employee’s point of view about the accelerated procedure, activy as an effective tool in seeking a quickly adjucation and finally efficient. Finally the proposal is the creation of special courts to trial of labor cases in progress before the accelerated procedure, as a tool to speed up the law activity and decrease the time of the labor case.